2019
DOI: 10.1002/brb3.1438
|View full text |Cite
|
Sign up to set email alerts
|

Human urinary kallidinogenase or edaravone combined with butylphthalide in the treatment of acute ischemic stroke

Abstract: AimThe effectiveness of neuroprotective agents is still unclear. Here we analyzed the clinical outcomes of acute ischemic stroke (AIS) patients treated with human urinary kallidinogenase (HUK) or edaravone (Eda) combined with butylphthalide (NBP).MethodsFrom January 2016 to December 2017, a total of 165 AIS patients were enrolled in this open‐label, randomized controlled clinical study. Patients were randomly allocated into HUK group and Eda group in a ratio of 2:1. All the patients received basic treatments a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Alternatively, mitochondrion is an organelle that plays roles in energy conversion and metabolism, and its dysfunction is the crucial pathophysiological change in ischemic stroke due to oxygen-glucose deprivation ( 14 ). It was found that a few studies have confirmed that NLRC4 ( 15 ), NLRP1 ( 16 ) and AIM2 ( 17 ) can promote cerebral ischemic injury, but there is no evidence that mitochondria can affect the pathological process of cerebral ischemia through them.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, mitochondrion is an organelle that plays roles in energy conversion and metabolism, and its dysfunction is the crucial pathophysiological change in ischemic stroke due to oxygen-glucose deprivation ( 14 ). It was found that a few studies have confirmed that NLRC4 ( 15 ), NLRP1 ( 16 ) and AIM2 ( 17 ) can promote cerebral ischemic injury, but there is no evidence that mitochondria can affect the pathological process of cerebral ischemia through them.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely used, but its clinical effect has certain limitations [ 3 , 4 ]. Butylphthalide sodium chloride can be used to improve the neurological deficit on acute ischemic stroke; in addition, it is a usual drug for curing acute ischemic stroke [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Jia et al ( 42 ) showed that butylphthalide improves the outcomes of patients with subcortical vascular cognitive impairment without dementia. Qian et al ( 43 ) showed that butylphthalide combined with kallidinogenase or edaravone enhanced the independence rate of patients with ischemic stroke. Future studies should examine those effects of butylphthalide in humans.…”
Section: Discussionmentioning
confidence: 99%